2005
DOI: 10.1007/s10265-005-0201-y
|View full text |Cite
|
Sign up to set email alerts
|

Paraphyly of Cyrtomium (Dryopteridaceae): evidence from rbcL and trnL-F sequence data

Abstract: Cyrtomium is an Asiatic genus characterized by anastomosing veins with included veinlets, and comprises about 40 species. We sequenced rbcL and trnL-F sequences of 19 species of Cyrtomium and eight species from related genera in order to elucidate a molecular phylogeny of the genus using maximum-parsimony methods. The phylogenetic trees did not agree with traditional classifications. Cyrtomium was resolved as paraphyletic, and a clade including subseries Balansana of Cyrtomium, Cyrtogonellum, Polystichum subac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
5
32
1
1
Order By: Relevance
“…3 ), albeit with no statistical support. This resolution contrasts with results from previous studies ( Lu et al 2005Li et al 2008 ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…3 ), albeit with no statistical support. This resolution contrasts with results from previous studies ( Lu et al 2005Li et al 2008 ).…”
Section: Discussioncontrasting
confidence: 56%
“…Cyrtogonellum caducum Ching, AY736350, Lu et al (2005) ; Cyrtogo nellum falcilobum Ching ex Y. T. Hsieh, DQ202409, Li et al (2008) ; Cyrtogonellum fraxinellum (Christ) Ching, AY736349, Lu et al (2005) ; Cyrtogonellum inaequalis Ching, AY736351, Lu et al (2005) ; Cyrtogonellum xichouense S. K. Wu & Mitsuda, EU106595, Li et al (2008) ; Cyrtomidictyum lepidocaulon (Hook.) Ching, EF177266, Driscoll and Barrington (2007) , DQ150392, Li et al (2007) ; Cyrtomium balansae (Christ) C.…”
Section: Acknowledgments This Project Was Partly Supported By Fundingmentioning
confidence: 99%
“…Sequences of poor quality were excluded if more than one accession per taxon was available. Phylogenetic reconstruction of this data was compared with published phylogenies of polystichoid ferns [27][28][29][30][31][32][33][34][35][36] to highlight any conflicts in the phylogenetic relationships observed. Comparisons were specifically made between our results and the consensus tree provided at the Polystichum website (http://www.uvm.edu/∼dbarring/polystichum.htm).…”
Section: Methodsmentioning
confidence: 99%
“…To address these questions, we assessed the reported occurrence of apomixis across ferns and reconstructed the evolution of apomixis in polystichoid ferns. The latter are an outstanding example given our knowledge on the phylogeny of this species-rich lineage of derived ferns [27][28][29][30][31][32][33][34][35][36], including the various reports on reticulate evolution and polyploidy [37], and reports on the reproductive biology of these ferns showing a range of modes from obligate outcrossing to apomixis [34,38,39]. It has been suggested that apomixis may be restricted to three lineages of polystichoid ferns which all have their putative origin in SE Asia [34].…”
Section: Introductionmentioning
confidence: 99%
“…Haplopolystichum by 24 accessions. Cyrtomium (sensu Zhang and Barrington, 2013b) and Phanerophlebia are both monophyletic (Li et al, 2008;Lu et al, 2005;Yatskievych, 1996;Yatskievych et al, 1988) and geographically more or less restricted to East Asia and southwestern U.S.A. to Central America, respectively. Therefore, we included only three species of Cyrtomium and two of Phanerophlebia in this study.…”
Section: Taxon Samplingmentioning
confidence: 99%